Job Flows, Worker Flows, and Churning - Burgess, Simon; Lane, Julia; Stevens, David (Journal of Labor Economics, 2000)
We utilize a large employer‐level panel dataset to explore the links between gross job flows and gross worker flows. Our findings have relevance for models of job creation and job destruction, and labor reallocation. We find churning flows (the difference between worker and job flows at the level of the employer) to be high, pervasive, and highly persistent within employers, suggesting that they arise as a correlate of an equilibrium personnel policy. We find the dynamic relationship between job and worker flows to be quite complex: lagged job flows raise churning flows, and lagged churning flows reduce employment growth.